Tennis meets Biomechanics - How biomechanical analysis can help elite tennis players and coaches to improve performance and prevent injuries - Martin, C. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
The serve is one of the most complex, important and traumatic strokes in tennis. In biomechanics, the serve is a sequence of motions referred to as a kinetic chain that begins with lower limb action. The presentation aims to present the secret of the serve concerning leg drive action to optimize serve performance and to present the methodology of serve biomechanical analysis developed for high-performance tennis players in the M2S Laboratory to optimize serve motion. Indeed, players and coaches need high-technology biomechanical tools that collect quantitative, objective and accurate data to improve serve performance and prevent injuries. 3D motion capture, radar and force platform are used to analyze serve performance. Kinematic and kinetic parameters are computed such as positions, angles and linear, angular velocities of upper and lower limb segments and joint loadings. A biomechanical report is provided to players and coaches with data reference. The practical implications for players and coaches are numerous: player`s longitudinal follow-up, evaluation of injury mechanisms and performance improvement. These aspects are demonstrated by practical examples for an individual scientific support for professional tennis players.